Structural and functional alterations of gut microbiome in mice induced by chronic cadmium exposure. (May 2020) - He, Xiwei; Qi, Zhaodong; Hou, Hui; Qian, Ling; Gao, Jie; Zhang, Xu-Xiang
Abstract: Mammalian gut microbiome is readily affected by acute or subchronic cadmium (Cd) intoxication, but it susceptibility following chronic Cd exposure at environmentally-relevant levels remains unknown. This study comprehensively assessed the effects of Cd exposure at doses of 10 and 50 ppm in drinking water for 20 weeks on gut microbiome in mice. Results showed that the Cd exposure induced alterations in gut morphology with potentially increased gut permeability and inflammation. These changes were accompanied by marked perturbation of gut microbiota characterized by significantly decreased gut microbial richness and lowered abundance of short chain fatty acid (SCFA)-producing bacteria, resulting in reduced SCFAs production in the gut. Moreover, the Cd exposure caused substantial metabolic functional changes of the gut microbiome, with significant inhibitions on gene pathways associated with metabolism of amino acid, carbohydrate, and energy, as well as promotions on metabolic pathways such as glutathione metabolism and aminobenzoate degradation. Our findings provide new insights into the hazards assessment of environmental Cd exposure towards gut microbiome. Highlights: Chronic Cd exposure induced gut barrier damage in mice. Chronic Cd exposure decreased gut microbial richness. Chronic Cd exposure inhibited SCFA-producing bacteria in mice gut. Chronic Cd exposure perturbed metabolic functions of gut microbiome.